The Interplay Of Macroeconomic Factor, Risk, And Bank Market Value: The Mediating Effect Of Profitability And The Moderating Role Of Size - Ardhianti, Christin; Lutfi, Lutfi (INVENTORY: JURNAL AKUNTANSI, 2025)
The research examines the interplay between macroeconomic factors, risk, and the market value of banks in Indonesia, with profitability acting as a mediator and bank size as a moderator. The study focuses on 24 conventional commercial banks listed on the Indonesia Stock Exchange from 2018-2023, totaling 170 bank-year observations. Using panel data analysis, the research tests how economic growth, credit risk, and liquidity risk affect bank market value, measured by Price-to-Book Value (PBV). Profitability, represented by Return on Assets (ROA), mediates the relationship between these factors and market value, with a specific focus on bank size's moderating role. The results show that profitability positively impacts market value, as do economic growth and liquidity risk, while credit risk has a negative effect. The study confirms that bank size strengthens the effect of profitability on market value but does not directly influence firm value. Robustness tests using Robust Standard Error and Generalized Method of Moments confirm the model's reliability. Policy implications suggest that banks should enhance profitability through effective risk management, especially credit risk, and leverage their size for competitive advantage. Practically, the findings stress the importance of liquidity management and macroeconomic stability in boosting bank market value in emerging economies.